Health Education Media Through Mandarin Language Posters in Increasing Knowledge and Local Food Consumption of Chinese Ethnic Children - Sopiyandi; Sely Sonia (Jurnal teknologi Kesehatan Borneo, 2023)
Nutritional problems in schoolchildren are often associated with food consumption patterns and behaviors at home and at school. Singkawang City has a variety of diversity, including ethnicity, one of which is ethnic Chinese. The culture of eating plays an important role because eating is seen as a family unifier as well as a clan unit (social structure) that affects the economic unity of the family. Increase a person's knowledge to get behavior changed by providing information about nutrition education through posters in Mandarin. This study aims to determine the effect of Chinese posters on the knowledge and consumption of local food of ethnic Chinese children at Asoka Elementary School, Bahussuta Foundation, Singkawang City. This research is a pre-experimental study with a one-group pre-test and post-test design and the purposeful sampling method. The sample of this study amounted to 26 4th grade students of Asoka Elementary School, aged 9–12 years. The instrument used was the Mandarin food poster instrument. Data collection was done by interview using a questionnaire and a 24-hour food recall form. The results showed that the average difference in knowledge before and after was 20.04, and the average difference in energy consumption (kcal) before and after was 203.09 kcal. There was an effect of knowledge (p = 0.000) and local food consumption before and after being given Chinese posters (p = 0.000). The conclusion is that there is an influence on knowledge and energy consumption (kcal) of local foods before and after being given posters in Mandarin.